FEATURES OF THE COURSE OF TONSILLITIS IN CHILDREN INFECTED WITH THE HERPES VIRUS - Olkhovska V.M.; Filatova A. А.; Yeloyeva Z. V. (World Science, 2020)
The article presents the features of the clinical course of tonsillitis caused by hemolytic streptococcus in children infected with human herpes simplex virus type 6 (HHV 6). It was revealed that tonsillitis in children with background infection with HHV 6 is characterized by a prolonged course, prolonged maintenance of fever, impaired general condition, the presence of signs of hepatomegaly and regional lymphadenitis, and as a result, a longer stay of such patients in the hospital. The characteristic clinical and laboratory features of tonsillitis in children infected with HHV 6 include the presence in the debut of the disease subfebrile body temperature, regional lymphadenopathy, hepatomegaly, thrombocytopenia, signs of a parenchymal reaction of the liver and mesadenitis. Latent HHV 6 infection in children affects the frequency of registration and the duration of certain symptoms of tonsillitis.